2020
DOI: 10.1136/gutjnl-2020-321277
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of gastroparesis, as documented in general practice records, in the United Kingdom

Abstract: ObjectiveTo generate real-world evidence for the epidemiology of gastroparesis in the UK, we evaluated the prevalence, incidence, patient characteristics and outcomes of gastroparesis in the Clinical Practice Research Datalink (CPRD) database.DesignThis was a retrospective, cross-sectional study. Prevalence and incidence of gastroparesis were evaluated in the CPRD database, with linkage to Hospital Episodes Statistics Admitted Patient Care and Office for National Statistics mortality data. Prevalence and incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
136
2
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(160 citation statements)
references
References 39 publications
(42 reference statements)
9
136
2
13
Order By: Relevance
“…4,[8][9][10][11][12][13]16,17,20 Bloating is a common symptom of functional digestive disorders including FD and IBS, but its prevalence is high in gastroparesis patients. 24 In these cohorts, the idiopathic subgroup is the largest, but a high prevalence of gastroparesis is found among diabetic patients, with 25 and 38% of patients identified in the respective studies. 23,24 Gastroparesis occurs more frequently in type 1 diabetes compared to type 2.…”
Section: Grade Bmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[8][9][10][11][12][13]16,17,20 Bloating is a common symptom of functional digestive disorders including FD and IBS, but its prevalence is high in gastroparesis patients. 24 In these cohorts, the idiopathic subgroup is the largest, but a high prevalence of gastroparesis is found among diabetic patients, with 25 and 38% of patients identified in the respective studies. 23,24 Gastroparesis occurs more frequently in type 1 diabetes compared to type 2.…”
Section: Grade Bmentioning
confidence: 99%
“…126,127 In the analysis of the UK CPRD database, mortality risk was higher in diabetic compared to idiopathic gastroparesis patients (adjusted hazard ratio: 1.9, 95% CI: 1.2-3.0). 24 A population-based study compared the observed and expected mortality of patients with gastroparesis, demonstrating a significantly higher death rate in patients compared to age-and sexmatched controls, which was largely due to cardiovascular comorbidity in diabetic patients. 23…”
Section: Grade Bmentioning
confidence: 99%
“…In fact, morphological and functional evidence suggests that it is by far most often the dysfunction of ICC and neurons that underlies impaired gastric emptying in the absence of mechanical obstruction, which is the clinical definition of gastroparesis 6 - 9 . Although estimates on the prevalence and burden of gastroparesis vary widely between studies, it is undoubtedly a frequent and disabling chronic medical condition 10 - 12 . Besides alleviating symptoms, most therapeutic strategies in gastroparesis intend to restore gastric emptying.…”
Section: Introductionmentioning
confidence: 99%
“…Of those with gastroparesis, 37.5% were caused by diabetes statistically, while patients with DGP had an almost 2 fold mortality to those with idiopathic gastroparesis. [ 11 ] With the prevalence of diabetes increases year by year, the number of DGP keeps growing. DGP can lead to slump decline on productivity of individuals and heavy economic burdens on social healthcare resources.…”
Section: Introductionmentioning
confidence: 99%